Additive manufacturing of ceramic components for façade construction - Cruz, Paulo J. S. (2020)
Additive Manufacturing (AM) opens new fields of research and development in the architectural design and construction industry, enabling a geometric freedom that can result in the design of components with specific requirements and multifunctional behaviours. This work explores the integration of digital design tools and AM extrusion processes on the production of ceramic architectural components for façade construction, reshaping and expanding the boundaries of what is possible to achieve with masonry construction in a wide range of applications (opaque walls, ventilated sunscreens, and shading systems). Several stoneware prototypes were developed, encompassing different challenges such as the morphology customisation, the versatility of use, the exploitation of the maximum degree of curvature, and the optimisation of structural patterns.